2023
DOI: 10.1128/spectrum.04912-22
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Method for the Clinical Visualization and Rapid Identification of Multidrug-Resistant Candida auris

Abstract: Candida auris is a highly lethal, multidrug-resistant, invasive fungus. However, conventional methods of C. auris identification are time-consuming and laborious and have low sensitivity and high error rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Although the time to results is short and the cost of analysis is affordable (Dhiman et al, 2011 ), this assay still requires an expensive analyzer and trained technicians thus limiting broad availability of the method. Molecular amplification-based methods, such as Polymerase Chain Reaction (PCR) or Loop-Mediated Amplification Method (LAMP), are also powerful tools and accurate for Candida auris identification (Yamamoto et al, 2018 ; Alvarado et al, 2021 ; Mulet Bayona et al, 2021 ; Zhang et al, 2023 ). However, commercially available kits are mainly used in positive blood cultures or other direct samples considering their high cost (Lockhart et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the time to results is short and the cost of analysis is affordable (Dhiman et al, 2011 ), this assay still requires an expensive analyzer and trained technicians thus limiting broad availability of the method. Molecular amplification-based methods, such as Polymerase Chain Reaction (PCR) or Loop-Mediated Amplification Method (LAMP), are also powerful tools and accurate for Candida auris identification (Yamamoto et al, 2018 ; Alvarado et al, 2021 ; Mulet Bayona et al, 2021 ; Zhang et al, 2023 ). However, commercially available kits are mainly used in positive blood cultures or other direct samples considering their high cost (Lockhart et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Jacques F. Meis et al identified C. auris at the level of different clades through high-resolution mass spectrometry ( Jamalian et al, 2023 ) and this provides us with new tools for faster and more accurate identification for a rapid response to nosocomial C. auris infection and to trace the source of the infection. In addition, YANG et al applied recombinase-aided amplification combined with lateral flow strips (RAA-LFS) to detect C. auris and successfully developed a rapid and effective method for this purpose ( Zhang et al, 2023 ). In conclusion, C. auris identification methods that are faster, cheaper, and have higher resolutions remain the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…From these 62 articles, only 25 represented original research papers [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Molecular Assays Used For the Active Surveillance Of ...mentioning
confidence: 99%